Cytomegalovirus Infection in Patient with Clear Cell Renal Cell Carcinoma - Ikhwan Rinaldi; Abdul Muthalib; Januar Widodo Sutandar; Hendro Adi Kuncoro; Bambang Irawan Harsono; Nelly Susanto; Tjondro Setiawan; Kevin Winston; Idham Rafly Dewantara; Ihya Fakhrurizal Amin; Yuli Maulidiya Shufiyani (Case Reports in Medicine)
Introduction. Cytomegalovirus (CMV) infection is a widespread condition that can affect individuals of all ages. Most cases of CMV infection are mild and resolve on their own. However, in immunocompromised individuals, such as post-transplant patients or those with cancer, severe infections can occur. While there have been several studies on CMV infection in post-transplant patients, there is limited literature on CMV infection in cancer, particularly in kidney cancer. Case Report. In this case report, we present the case of a 61-year-old man with clear cell renal cell carcinoma who underwent targeted therapy with the receptor tyrosine kinase (RTK) inhibitor lenvatinib and the mammalian target of rapamycin (mTOR) inhibitor everolimus. The patient was hospitalized for 26 days and admitted to the intensive care unit (ICU) due to shortness of breath, decreased oxygen saturation, and irregular breathing. Cytomegalovirus polymerase chain reaction (PCR) test results were positive. Given the high prevalence of CMV infection in developing countries, it is likely that the patient had a reactivation of CMV. As such, the patient was subsequently treated with ganciclovir for 14 days and showed improvement in symptoms such as shortness of breath, cough, fever, and increased oxygen saturation. Following recovery, the patient received maintenance therapy with oral valganciclovir for 7 days. No further symptoms appeared during subsequent cancer treatments. Conclusion. Cancer patients who are undergoing treatment are at a higher risk for developing opportunistic infections, which can result in morbidity and mortality. Therefore, healthcare professionals should be aware of the possibility of CMV infection in cancer patients and be prepared to diagnose and treat the infection, particularly in areas where the prevalence of CMV infection is high.